Iowa Birdline update, August 31, 1992 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1992)
Email for the Iowa Birdline update for August 31, 1992. Highlights of the update include sightings of twenty American Golden-Plovers and an early Broad-winged Hawk. Also included are handwritten notes for the next week's update with sightings of a flyover Mississippi Kite at Cordova Park and a male Black-throated Blue Warbler at Hickory Hill Park. Epson - sheet feed/flatbed